JME-001 phase II trial of first-line combination chemotherapy with cisplatin, pemetrexed, and nivolumab for unresectable malignant pleural mesothelioma - Nobukazu Fujimoto; Yosuke Miyamoto; Sae Wada; Katsuyuki Hotta; Toshiyuki Kozuki; Keisuke Aoe; Jun Sakurai; Michihiro Yoshida; Daijiro Harada (Journal for ImmunoTherapy of Cancer)
Background JME-001 is a phase II trial assessing the efficacy and safety of cisplatin, pemetrexed, and nivolumab as first-line therapy in malignant pleural mesothelioma (MPM).Patients and methods Patients with untreated, unresectable MPM with an Eastern Cooperative Oncology Group (ECOG) performance status (PS) of 0–1 were included. The primary endpoint is the centrally reviewed objective response rate. The secondary endpoints include (1) response rate assessed by investigators, (2) disease control rate, (3) overall survival, (4) progression-free survival, (5) duration of response, and (6) time to response. Safety and adverse events will also be evaluated. Cisplatin (75 mg/m2), pemetrexed (500 mg/m2), and nivolumab (360 mg/body) were administered intravenously every 3 weeks with a total of 4–6 cycles. If patients did not progress during the combination phase, maintenance therapy with nivolumab was administered until disease progression or unacceptable toxicity. Tissue samples were required and collected for programmed death ligand 1 analysis.Results Eighteen patients (mean age 69.2 years, 15 men) were enrolled between January 2018 and May 2019. The ECOG PS was 0 in 3 patients and 1 in 15 patients. Fourteen (77.8%; 95% CI 52.4% to 93.6%) patients had an objective response. The disease control rate was 94.4% (95% CI 72.7% to 99.9%). Fourteen (77.8%) patients had partial response (PR), three had stable disease, and one was not evaluable. Tumor shrinkage was observed in 10/14 (71.4%) patients with epithelioid, and 2/2 (100%) patients with sarcomatoid or biphasic histological subtype had PR. Ten (55.6%) patients experienced grade 3 or worse adverse events, including disorder of metabolism or nutrition (33.3%), loss of appetite (27.8%), anemia (16.7%), and hyponatremia (11.1%). No treatment-related deaths occurred.Conclusions The safety and efficacy of this study strongly support a definitive trial of this combination.Trial registration numberUMIN000030892.